Atypical Spitz tumours across age groups: clinicopathological features, management strategies and long-term outcomes in a 20-year retrospective cohort study - Fortunato Cassalia; Marcodomenico Mazza; Elena Guadagnini; Paolo Del Fiore; Laura Ventura; Elisa Galasso; Alessandra Buja; Rocco Cappellesso; Francesco Fortarezza; Andrea Danese; Gianni Bisogno; Franco Bassetto; et al. (Skin Health and Disease, 2026)
Abstract Background Atypical Spitz tumours (ASTs) sit between Spitz naevi and spitzoid melanoma; age may modulate morphology and outcome. Objectives To compare recurrence-free survival (RFS) across prespecified age groups and test associations with histological aggressiveness and sentinel lymph node biopsy (SLNB) status. Methods A retrospective cohort study of patients with ASTs was carried out at two Italian tertiary centres (1 January 2002–31 December 2022). Patients were grouped according to age: ≤18, 19–25, 26–39 and ≥40 years. The primary endpoint was RFS from definitive excision. The secondary endpoints were Breslow thickness, mitotic rate and SLNB positivity. Kaplan–Meier and nonparametric tests were carried out; data were missing in <5% of cases. Results A total of 187 patients (57 male and 130 female individuals; mean age 37 years) were included. Mean Breslow thickness (2.33 mm in patients aged ≤18 years vs. 0.88 mm in patients aged ≥ 40 years; P < 0.001) and mean mitotic activity (1.89 mitoses mm–2 in patients aged ≤18 years vs. 0.15 mitoses mm–2 in patients aged ≥ 40 years; P < 0.001) decreased with age. Of 148 patients who underwent re-excision, 44 (29.7%) underwent SLNB; 12 of 44 (27%) were positive (42% in children; 9% in adults). Median follow-up was 40 months (interquartile range 18–79); one local recurrence occurred in a 47-year-old patient, later reclassified as conventional melanoma. There were no distant metastases or melanoma-related deaths. Five-year RFS was 100% for patients aged ≤ 39 years and 98% for those aged ≥ 40 years (log-rank P = 0.30). SLNB positivity did not predict recurrence (0/12 positive vs. 1/32 negative). Conclusions Across this 20-year, dual-centre series, ASTs had excellent outcomes at all ages. Paediatric ASTs were thicker and more mitotically active yet clinically indolent. These findings support conservative excision without routine SLNB in children and a selective, multidisciplinary approach in adults.